1996
DOI: 10.1111/j.1476-5381.1996.tb15562.x
|View full text |Cite
|
Sign up to set email alerts
|

B1 bradykinin receptors and sensory neurones

Abstract: 1 The location of the B, bradykinin receptors involved in inflammatory hyperalgesia was investigated.2 No specific binding of the B1 bradykinin receptor ligand [3H]-des-Arg10-kallidin was detected in primary cultures of rat dorsal root ganglion neurones, even after treatment with interleukin-l1 (100 iu ml-'). 3 In dorsal root ganglion neurones, activation of B2 bradykinin receptors stimulated polyphosphoinositidase C. In contrast, B1 bradykinin receptor agonists (des-Arg9-bradykinin up to 10 pM and des-Arg'0-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…In the present study, we have shown that the size of this component is selectively facilitated in the presence of des-Arg 9 -BK, a specific agonist of the B1 receptor. Unlike neurokinin-receptor activation (36), des-Arg 9 -BK did not directly depolarize the ventral root when applied in vitro (37). The facilitation, which recovered within 20 min after washout of des-Arg 9 -BK, was not observed in isolated spinal cords obtained from B1-receptor knockout mice.…”
Section: Discussionmentioning
confidence: 88%
“…In the present study, we have shown that the size of this component is selectively facilitated in the presence of des-Arg 9 -BK, a specific agonist of the B1 receptor. Unlike neurokinin-receptor activation (36), des-Arg 9 -BK did not directly depolarize the ventral root when applied in vitro (37). The facilitation, which recovered within 20 min after washout of des-Arg 9 -BK, was not observed in isolated spinal cords obtained from B1-receptor knockout mice.…”
Section: Discussionmentioning
confidence: 88%
“…Activation of bradykinin B 2 receptors on sensory nerves produces pain and hyperalgesia by depolarization and sensitization of nerve fibers to physical stimuli (heat and mechanical), whereas activation of B 2 receptors on other tissues such as sympathetic nerves and inflammatory cells stimulates the production of proinflammatory mediators such as prostanoids and cytokines (Dray, 1997). The B 1 receptor, for which the major metabolite of bradykinin des-Arg 9 -bradykinin has a greater affinity than the parent peptide, is expressed under inflammatory conditions and plays a prominent role in inflammatory hyperalgesia by actions on targets other than sensory nerves (Dray and Perkins, 1993;Davis et al, 1996). The involvement of both B 1 and B 2 receptors in inflammatory hyperalgesia suggests that kinin antagonists might be useful analgesics in such conditons.…”
Section: Antagonists For Inflammatory Mediatorsmentioning
confidence: 99%
“…Most of these cells effects are connected with the activation of B 2 receptors, since only these receptors were found to be located on nociceptive neurons [6,7]. However, more recently, it has been found that activation of B 1 receptors, located on other than sensory cells, may be responsible for the release of mediators sensitizing or activating nociceptors [8]. Furthermore, the existence of B 1 receptors on dorsal horn neurons in the spinal cord as well as on bipolar neurons of the dorsal root ganglia was also demonstrated [9].…”
Section: Introductionmentioning
confidence: 99%